2017
DOI: 10.1186/s40409-017-0125-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of jellyfish venom fibrin(ogen)olytic enzymes from Nemopilema nomurai

Abstract: BackgroundBecause jellyfish are capable of provoking envenomation in humans, they are considered hazardous organisms. Although the effects of their toxins are a matter of concern, information on the venom components, biological activity and pathological mechanisms are still scarce. Therefore, the aim of the present study was to investigate a serine protease component of Nemopilema nomurai jellyfish venom (NnV) and unveil its characteristics.MethodsTo determine the relationship between fibrinolytic activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…By functional assay (using fibrinolytic activity in zymography assay), Bae et al [ 99 ] reported venom proteins of Nemopilema nomurai as characterized by MW of approximately 70, 35, 30, and 28 kDa. These authors compared N. nomurai with Aurelia aurita venoms, with similar banding patterns, distributed in 60–80 kDa and 25–37 kDa size bands, and with the siphonophoran Physalia physalis venom, with MW > 25 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…By functional assay (using fibrinolytic activity in zymography assay), Bae et al [ 99 ] reported venom proteins of Nemopilema nomurai as characterized by MW of approximately 70, 35, 30, and 28 kDa. These authors compared N. nomurai with Aurelia aurita venoms, with similar banding patterns, distributed in 60–80 kDa and 25–37 kDa size bands, and with the siphonophoran Physalia physalis venom, with MW > 25 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…The chromatography on DEAE-sepharose at pH = 10.0 has revealed the presence of active enzymes with a molecular weight of more than 45 kDa. Given our previous results on the presence in the tissues of hydrobionts of enzymes capable of cleaving fibrinogen [12], as well as the result of Bae et al [13], which revealed a chymotrypsin-like serine protease with fibrinolytic activity in the venom of jellyfish, all obtained fractions were tested by enzyme-electrophoresis with fibrinogen. To date, the search for available sources of fibrino(geno) lytic enzymes is quite relevant.…”
Section: Resultsmentioning
confidence: 99%
“…Rhizoprotease, a new metalloproteinase of 95 kDa, was isolated in the venom [ 61 ]. Nemopilema nomurai (scyphozoan) venom contains a chymotrypsin-like serine protease with fibrinolytic activity [ 62 ]. Aurelia aurita shows strong fibrinogenolytic activity [ 63 ].…”
Section: Pathophysiologymentioning
confidence: 99%